PROGRAM RISET ILMIAH IMRE LAKATOS - Mustansyir, Rizal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
The topic of this paper is related to the methodological thought of a philosopher Imre Lacatos. The methodological problem is a core problem in the area of philosophy of science. Science philosopher’s discourse shows the methodology of science as one of the scientific procedures in gaining the truth, but in fact, it caused the emergence of methodological mainstream; mono-methodology and pluri-methodology. Imre Lacatos’ tried to mediate the discourse of two fortifications by means of scientific research program. Some ideas developed by Lacatos’ in its relation to the scientific research programs are; first, Lacatos propose a sum of mathematics knowledge which is based on the heuristics idea, second, Lacatos’ criticism to Popper’s falsifiable concept, third, Lacatos’ effort in looking for a harmonious method that provides a sum of rational scientific progress, appropriately keeps its consistency with the historical fact, fourth, Lacatos’ connect the research program to scientists who protect the core of theory from falsification effort, fifth, a research program is qualified as progressive if it is signed by stunning novel facts and as deteriorative if the program is not directed to the new fact, sixth, the hard-core is determining characteristic of program, it is a general theory of hypotheses which is employed as a foundation of developed program, seventh, the negative heuristic of hard-core program is detailed program which states the basic assumption of program, eighth, the positive heuristic of hard-core program is an outline which indicates how the research program can be developed under additional assumption of new phenomenon clarification.